2014
DOI: 10.1007/s12013-014-0440-4
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty: Leg Length Discrepancy Affects Functional Outcomes and Patient’s Gait

Abstract: Our study was targeted to investigate the relationship between postoperative leg length discrepancy (LLD) and the outcomes of total hip arthroplasty (THA) including gait, hip function, and lower back pain (LBP). Ninety-two patients who underwent primary THA during Jan 2009 to Apr 2011 in our medical center were enrolled in this study. We measured postoperative LLD of the patients both directly and from the leg radiographs. Six months after the surgery, we evaluated the hip function with Harris Hip Score (HHS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 14 publications
2
30
0
1
Order By: Relevance
“…When traditional standing position cannot be applied, the normal angle of lower limb mechanical axis passes the center of the tibial plateau is around 57.8% [6,7], which is one of the important standard value to assess arthroplasty surgery. Another important standard value is the mechanical deviation between the lower limb mechanical axis and the center of the tibial plateau, of which less than 5 mm defines excellent and 5-10 mm defines normal [8][9][10]. Using different position for DR images results greatly different measured data, and our results show that the application of improved position is more suited for arthroplasty surgeries.…”
Section: Discussionmentioning
confidence: 79%
“…When traditional standing position cannot be applied, the normal angle of lower limb mechanical axis passes the center of the tibial plateau is around 57.8% [6,7], which is one of the important standard value to assess arthroplasty surgery. Another important standard value is the mechanical deviation between the lower limb mechanical axis and the center of the tibial plateau, of which less than 5 mm defines excellent and 5-10 mm defines normal [8][9][10]. Using different position for DR images results greatly different measured data, and our results show that the application of improved position is more suited for arthroplasty surgeries.…”
Section: Discussionmentioning
confidence: 79%
“…Soft, custom-made insoles alleviate pain by reducing the sole parts that are under pressure. In addition, limping while walking results from leg length discrepancy (LLD) in more than half of the study group, which causes pain and damage to the spine [ 19 ]. Insoles that provide additional height can compensate for LLD, and the secondary effects can mostly be eliminated [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although proper implant reconstruction improves the biomechanical function of the hip, existing evidence on the association with clinical outcomes is not consistent. Several studies using patientreported outcome measures (PROMs) have found no association with radiographic measurements after THA (1, [8][9][10][11][12][13][14] whereas others have reported marginally significant correlations (7,9,15,16). In addition to PROMs, functional tests can be used to assess outcomes after THA.…”
Section: Introductionmentioning
confidence: 99%
“…Asayama et al (5) demonstrated that a 15% decrease in femoral offset generates weakness of the abductor muscles and correlates with the frontal plane tilt angle of the pelvis during the Trendelenburg test (17). Sariali et al (18) found significant gait alterations in patients with more than 15% decreased postoperative femoral offset while Zhang et al (16) and Li et al (19) reported significant gait alterations between patients with variable LLD after THA. Because PROMs are subjective measures, suffer from a ceiling effect, and may lack sufficient sensitivity to demonstrate a difference in clinical outcomes (18,20), functional tests may be better discriminators to capture functional impairments in relation to changes of the reconstructed hip joint position after THA.…”
Section: Introductionmentioning
confidence: 99%